Lung Cancer Survival in Lithuania: Changes by Histology, Age, and Sex From 2003-2007 to 2008-2012. (8th May 2019) - Gedvilaitė, Vaida; Danila, Edvardas; Cicėnas, Saulius; Smailytė, Giedrė
Lung cancer is the most common cancer-related death worldwide. The aim of this study is to describe the most recent survival rates by sex, age group, extent of disease, and histology of lung cancer in Lithuania. The study is based on the Lithuanian Cancer Registry database. The analysis included patients with primary invasive lung cancer diagnosed in 1998 to 2012 (International Classification of Diseases, Tenth Revision C33 and C34). Patients were followed up with respect to vital status until December 31, 2012. Five-year relative survival estimates were calculated using period analysis. Relative survival was calculated as the ratio of the observed survival of patients with cancer and the expected survival of the underlying general population. In our study, the overall 5-year relative survival was low but increased slightly (10.7%) from 2003–2007 to 2008–2012. Positive changes in survival were evident in both sexes, in almost all age groups and for all histological groups and disease stages. Adenocarcinoma relative survival increased from 6.7% in 2003–2007 to 12.8% in 2008–2012 and squamous cell carcinoma increased from 7.4% in 2003–2007 to 11.1% in 2008–2012. Patients with small-cell carcinoma had the worst survival (2.9% in 2003-2007 and 3.6% in 2008–2012). The majority of patients with lung cancer are diagnosed with advanced disease. The number of new cases of advanced lung cancer increased from 35.1% to 37.8%. Despite low overall survival, there were positive changes in survival in both sexes, in almost all age groups, and for all histological groups and disease stages. The survival rate of patients with lung cancer in Lithuania is similar to that in other European countries.